Menschen(un)würdig Altern im Gefängnis - Wilde, Frank; Ghanem, Christian (Über Mauern blicken - 25 Jahre Forschen im Justizvollzug: Festschrift für Ueli Hostettler zum 65. Geburtstag, 2025)
As society ages, prison populations are also changing—and presenting the prison system with new challenges that have received little attention to date. This article examines the living conditions of older prisoners, their specific needs, and the structural barriers they encounter in a prison system geared toward young men. Issues such as care needs, social isolation, a lack of age-appropriate services, and dying in prison clearly show that fundamental structural changes are necessary. There is a need for an evidence-based criminal policy discourse that focuses on both the integration and self-determination of older prisoners. The research work of Ueli Hostettler and the Prison Research Group has provided important impetus for a practice that takes aging and human dignity seriously, even behind bars. (machine translation)